Expanding horizons in burn care: a new paradigm for General Surgeons in Brazil - KELLY DANIELLE DE ARAÚJO; ROBERTO MENDES FERREIRA (Revista do Colégio Brasileiro de Cirurgiões, 2024)
ABSTRACT The role of the burn surgeon in Burn Treatment Centers (BTCs) is crucial for complementing the multidisciplinary approach in the treatment of burn patients. Globally, the areas of General Surgery and Plastic Surgery are the primary surgical specialties dedicated to this function. The structuring of the Burn Patient Care Line in Minas Gerais highlighted the need to expand the “Burn Care” Field of Expertise, extending it to General Surgery. With the inevitable expansion of the Care Line, pioneered by the state of Minas Gerais, to the federal level, the need for specialized surgical training encompasses both the state context and anticipates the national scenario in the short term. Therefore, the expansion of the “Burn Care” Field of Expertise is fundamental to meeting specific demands and improving the quality of care offered to burn patients, in accordance with international standarts.